Mobile labour: an introduction - Bastos, Cristiana (2021)
Mobility has been in the academic spotlight at least since the 1980s, in the wake of globalisation studies (Salazar 2013), together with post-modern trends, which called for a theoretical breach in an academic scene dominated by perspectives on structures, territory and stasis (examples of this breach can be found in Clifford 1997; Deleuze and Guattari 1987; de Certeau 1984; Virilio 1986). In this context, ‘the nomad – whether traveller, refugee, runaway’ became ‘the symbolic identity of our age’, as suggested by Kendal, Woodward and Skrbis (2009, 85). At the turn of the millennium, the world was portrayed as revolving around movement and migration, transnationalism and hybridism, networks and cosmopolitanism, liquidity and fluidity, nomads and runaways (Salazar 2020). Metaphorized as proximity and togetherness, along with cultural exchange, hybridism, networks, connectedness and cosmopolitanism, mobility was perceived by many as positive and as reducer of inequality gaps. Just as social mobility was systematically translated to its upwards trajectory towards the erasure of social, economic, and cultural inequality, physical mobility was conceived along the same lines, having the potential to challenge the ‘old’ boundaries of nationalism, ethnicity, race and even gender. In a word, mobility was equated to the promise of a more cosmopolitan, ethical, better world.